Preparation of Co-coated NC supported ruthenium metal catalyst and application of Co-coated NC supported ruthenium metal catalyst in selective hydrogenation reaction of benzoic acid

The Co@NC-supported ruthenium metal catalyst solves the problem of high cost and reduced selectivity of existing catalysts in the selective hydrogenation reaction of benzoic acid, and achieves high conversion and high selectivity cyclohexanoic acid generation, which extends the catalyst Lifespan and reduce industrial costs.

CN119259035APending Publication Date: 2025-01-07TAIZHOU UNIV (ZHEJIANG)
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202210386980.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing catalysts have problems of high cost, reduced selectivity and reduced catalyst activity in the selective hydrogenation reaction of benzoic acid, especially under high reaction conditions, which leads to serious loss of precious metals and increased side reactions.

Method used

Using Co@NC-supported ruthenium metal catalyst, a stable matrix is ​​formed to disperse ruthenium ions by mixing in a magnetic stirrer and vacuum drying and high-temperature calcination, thereby improving the stability and activity of the catalyst, and maintaining catalytic activity at high temperatures. Reduce the hydrogenation activity of the benzene ring to improve selectivity.

Benefits of technology

High conversion and high selectivity catalyzing the formation of cyclohexanoic acid into cyclohexanoic acid, extending the service life of the catalyst, reducing industrial costs, and reducing the occurrence of side reactions, and having an environmentally friendly process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HSA0000271062930000011
    Figure HSA0000271062930000011
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, and provides preparation of a Co-coated NC supported ruthenium metal catalyst and application of the Co-coated NC supported ruthenium metal catalyst in selective hydrogenation reaction of benzoic acid. The method comprises the following steps: adding benzoic acid and a Co-NC supported ruthenium catalyst into a high-pressure reaction kettle, and hydrogenating with benzoic acid in the high-pressure reaction kettle to obtain cyclohexanecarboxylic acid. The mass ratio of benzoic acid to the catalyst is 24: (1-6); hydrogen is used for replacement, and the hydrogen pressure ranges from 0.1 MPa to 2 MPa; the reaction temperature ranges from 333 K to 353 K; and stirring and reacting for 0.5-1 hour to obtain the product cyclohexanecarboxylic acid. Data of the embodiment of the invention show that the conversion rate of benzoic acid hydrogenation provided by the invention is 63.8%-98.6%, and the selectivity of cyclohexanecarboxylic acid is 75.6%-99.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and proposes the preparation of a Co@NC-loaded ruthenium metal catalyst and the application of the catalyst in the selective hydrogenation reaction of benzoic acid. Background Art

[0002] Cyclohexanecarboxylic acid and its derivatives are important organic chemical raw materials and drug intermediates, and have wide application value in drug synthesis and new material research and development. For example, cyclohexanecarboxylic acid can be used in the synthesis of praziquantel, a drug for the treatment of schistosomiasis, and can also be used to prepare the photocuring agent 1-hydroxycyclohexylphenyl ketone. It is an efficient, yellowing-resistant free radical solid photoinitiator, known as one of the most important free radical photoinitiators in modern industry. It has the advantages of long storage time, high initiation efficiency, and a wide range of ultraviolet absorption. It is widely used in paper, metal, plastic, building materials, coatings and other fields. Its derivatives, such as trans-4-isopropylcyclohexanecarboxylic acid, are important intermediates for the synthesis of nateglinide, a drug for the treatment of diabetes.

[0003] Green chemistry has become the trend of scientific research and production today. Catalytic hydrogenation reactions usually generate products and water. If properly controlled, other by-products are rarely generated, so they meet the requirements of high atomicity and green chemistry. At present, the production of cyclohexylcarboxylic acid is made by metal selective catalytic hydrogenation of benzoic acid. The selective hydrogenation of benzoic acid to produce cyclohexylcarboxylic acid is one of the important steps in the toluene process of SNIA to prepare caprolactam. Commonly used catalysts include Pd / C, Ru / C, Rh-Pi, Ni / SiO2, etc., and Pd / C is the most used. However, since this type of catalyst is in powder form, it is difficult to separate from the reaction raw materials and products. In order to ensure the separation efficiency of the product and the catalyst, it is usually required to completely convert benzoic acid to reduce the subsequent processing steps. Therefore, it is necessary to use multiple gold series to react, which is not only complicated in process, but also leads to an increase in side reactions and a decrease in selectivity; at the same time, the catalyst loss during filtration separation and regeneration is also large, and the loss of precious metals is serious. It is at a disadvantage in terms of cost.

[0004] The selective benzene ring hydrogenation reaction of benzoic acid is the most direct and effective method for synthesizing cyclohexanecarboxylic acid, but the hydrogenation of benzoic acid needs to overcome the high resonance energy of the benzene ring. On the other hand, the benzene ring is connected to the electron-withdrawing group so that the hydrogenation requires more stringent conditions than the electron-donating group, which will cause some undesirable side reactions to occur, such as the carboxyl group on the benzene ring being hydrogenated to a hydroxyl group. At present, people mainly use noble metal catalysts to catalyze the reaction of benzoic acid hydrogenation to generate cyclohexanecarboxylic acid. Most catalysts use a loaded method to disperse the metal active center, thereby more effectively improving the utilization rate of the metal. Among them, the active center is mainly Pt family noble metals Pd, Pt, Rh, Ir, Ru. Among the noble metals, Pd has the characteristics of high catalytic activity, high selectivity, long service life, and not easy to deactivate, making it the most widely used in hydrogenation reactions.

[0005] At present, the main problems in the preparation of cyclohexanecarboxylic acid by hydrogenation are as follows: (1) The cost of using precious metals to prepare catalysts is high. (2) Some of the added ligands are not very stable, which will lead to an increase in side reactions and a decrease in selectivity. (3) When the reaction conditions are high, the catalyst activity will decrease.

[0006] Based on the above, there is an urgent need to design an environmentally friendly catalyst to improve the conversion rate of benzoic acid and the selectivity of benzene ring, which has great industrial significance. Summary of the invention

[0007] The purpose of the present invention is to provide a preparation method of a Co@NC-loaded ruthenium metal catalyst and its application in the selective hydrogenation reaction of benzoic acid. The catalyst prepared by the method has the advantages of good active component dispersibility and stable catalyst performance, thereby increasing the service life of the catalyst, and has good activity and high benzene ring selectivity.

[0008] In order to achieve the above-mentioned invention object, the present invention provides the following specific solutions:

[0009] 1) Mix the prepared Co@NC precursor materials in a beaker and stir on a magnetic stirrer for 12 to 36 hours;

[0010] 2) The mixed solution obtained in step 1 is filtered and washed, and then vacuum dried at 40 to 100 degrees for 3 to 16 hours to obtain a sample.

[0011] 3) The sample obtained in step 2 is subjected to high temperature calcination under an inert gas to obtain a sample.

[0012] 4) The sample obtained in step 3 is mixed with the ruthenium precursor solution and stirred on a magnetic stirrer for 8 to 16 hours, and the mixed solution is reduced, filtered, washed and dried to obtain a Co@NC-loaded ruthenium metal catalyst.

[0013] In step 1) of the present invention, the raw materials for preparing the Co@NC structure are selected from cobalt chloride, cobalt bromide, cobalt iodide, cobalt acetate, cobalt carbonate, cobalt sulfate; carboxymethyl cellulose, methyl cellulose, polyvinyl alcohol, sodium alginate, N-methylpyrrolidone; potassium thiocyanide, potassium ferrocyanide, potassium hexacyanocobaltate; four of ethanol, methanol, formamide, and acetone, preferably cobalt acetate, carboxymethyl cellulose, potassium hexacyanocobaltate, and ethanol.

[0014] In step 1) of the present invention, the drug mass of cobalt acetate is 1.2368-2.5462 g, carboxymethyl cellulose is 4-8 g, potassium hexacyanocobaltate is 1.9873-3.1621 g, and ethanol is 50-150 ml. The preferred drug mass is cobalt acetate 1.6873-2.1321 g, carboxymethyl cellulose 5-7 g, potassium hexacyanocobaltate 2.3146-1.8431 g, and ethanol 75-125 ml. The stirring time is 12-36 h, and the preferred stirring time is 20-28 h.

[0015] In step 2) of the present invention, the vacuum drying temperature is 40-100° C. and the time is 3-16 hours, preferably the drying temperature is 60-80° C. and the time is 8-12 hours.

[0016] In step 3) of the present invention, the inert gas is one or more of argon, helium, and nitrogen; the calcination temperature is 500-1100° C., and the time is 1-7 hours, preferably 600-1000° C., and the time is 2-6 hours.

[0017] In step 4) of the present invention, the ruthenium precursor is selected from one of ruthenium acetylacetonate, ruthenium acetate, potassium chlororuthenate, ruthenium trichloride, ruthenium oxide, and ruthenium iodide, preferably ruthenium acetate, and the content of ruthenium metal in the catalyst is 1-2wt%, preferably 1.2-1.5wt%. The raw material used in the reduction step is selected from one of potassium borohydride, stannous chloride, oxalic acid, and potassium permanganate, preferably potassium borohydride, and the drug mass taken is 20-100mg, preferably 50-70mg.

[0018] The present invention utilizes the characteristic of Co@NC forming a stable matrix to disperse and fix ruthenium ions, thereby improving the stability and activity of the catalyst. The present invention utilizes the stable structure of the Co@NC structure to load ruthenium metal, so that it cannot agglomerate, and can obtain uniform and highly dispersed active centers, which can improve the catalytic activity of the catalyst; the reaction solution of the present invention is water, which reduces the pollution caused to the environment by harmful solvents such as benzene; the Co@NC structure-loaded ruthenium metal catalyst of the present invention does not reduce the catalytic activity at high temperature, and can also expose more active sites, which is beneficial to improve the catalytic activity of the catalyst. The Co@NC structure-loaded ruthenium metal catalyst prepared by the present invention has high activity for hydrogenation of benzene rings, but low catalytic activity for hydrogenation of carboxyl groups, so it can catalyze the highly selective hydrogenation of benzoic acid to generate cyclohexanecarboxylic acid. The Co@NC structure-loaded ruthenium metal catalyst prepared by the present invention is a Co@NC structure-loaded ruthenium metal catalyst. Compared with other precious metals, the price of ruthenium metal is lower, which can reduce industrial costs. It is an efficient and green process with good application prospects in industry. The results of the examples show that when the Co@NC structure-supported ruthenium metal catalyst provided by the present invention is used to hydrogenate benzoic acid to prepare cyclohexanecarboxylic acid, the conversion rate of benzoic acid hydrogenation can reach 98.6%, and the selectivity of cyclohexanecarboxylic acid is 75.6% to 99.7%. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a graph showing the benzoic acid conversion rate and cyclohexanecarboxylic acid selectivity in the selective hydrogenation of benzoic acid to cyclohexanecarboxylic acid over Co@NC-supported ruthenium metal catalyst. DETAILED DESCRIPTION

[0019] The following is a detailed description of the embodiments of the present invention. It is necessary to point out that the specific embodiments herein are only used to further illustrate the present invention and are not used to limit the present invention.

[0020] The Co@NC structure-supported ruthenium metal catalyst of the present invention is evaluated by hydrogenation reaction of benzoic acid in a high-pressure reactor. In the high-pressure reactor, water is used as a solution, the temperature is 80°C, the reaction pressure of 2MPa hydrogen, and the mass ratio of benzoic acid to the Co@NC-supported ruthenium catalyst is 24:1-6. Benzoic acid is hydrogenated to obtain cyclohexanecarboxylic acid. GC gas chromatograph is used for analysis.

[0021] Example 1

[0022] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0023] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0024] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0025] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0026] 5) Use a 1 ml pipette to transfer 1.450 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0027] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0028] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 98.6%, and the selectivity of cyclohexanecarboxylic acid was 99.7%. Figure 1 .

[0029] Example 2

[0030] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0031] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0032] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0033] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0034] 5) Use a 1 ml pipette to transfer 1.250 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0035] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0036] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 95.3%, and the selectivity of cyclohexanecarboxylic acid was 98.8%. Figure 1 .

[0037] Example 3

[0038] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0039] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0040] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0041] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0042] 5) Use a 1 ml pipette to transfer 1.000 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0043] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0044] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 90.5%, and the selectivity of cyclohexanecarboxylic acid was 96.7%. Figure 1 .

[0045] Example 4

[0046] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0047] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0048] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0049] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0050] 5) Use a 1 ml pipette to transfer 0.825 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0051] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0052] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 88.2%, and the selectivity of cyclohexanecarboxylic acid was 93.8%. Figure 1 .

[0053] Example 5

[0054] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0055] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0056] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0057] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0058] 5) Use a 1 ml pipette to transfer 0.560 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0059] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0060] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 80.8%, and the selectivity of cyclohexanecarboxylic acid was 90.3%. Figure 1 .

[0061] Example 6

[0062] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0063] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0064] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0065] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0066] 5) Use a 1 ml pipette to transfer 0.380 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0067] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0068] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 75.2%, and the selectivity of cyclohexanecarboxylic acid was 85.7%. Figure 1 .

[0069] Example 7

[0070] 1) Mix 1.652 g of cobalt acetate, 6 g of carboxymethyl cellulose, 2.413 g of potassium hexacyanocobaltate, and 200 ml of ethanol and stir for 26 hours to mix them evenly.

[0071] 2) The mixed solution obtained in step 1 was filtered and washed, and then vacuum dried at 80 degrees for 8 hours to obtain a sample.

[0072] 3) The sample obtained in step 2 was calcined in a nitrogen atmosphere at a temperature of 1000° C. for 4 h to obtain a sample.

[0073] 4) Weigh 10 g of ruthenium acetate and dissolve it in an aqueous solution, transfer it to a 100 ml volumetric flask, add deionized water to the corresponding scale, and prepare a ruthenium acetate solution with a mass concentration of 100 mg / mL.

[0074] 5) Use a 1 ml pipette to transfer 0.175 ml of the ruthenium acetate solution in step 4 and the sample obtained in step 3, and stir for 8 hours to mix them evenly.

[0075] 6) The mixed solution obtained in step 5 was reduced with 60 mg of potassium borohydride, filtered, washed, and dried to obtain the Co@NC-supported ruthenium metal catalyst.

[0076] 7) The Co@NC supported ruthenium metal catalyst obtained above was loaded into a high-pressure reactor, and water was used as a solution. Benzoic acid was hydrogenated to obtain cyclohexanecarboxylic acid at a temperature of 80°C, a reaction pressure of 2MPa hydrogen, and a mass ratio of benzoic acid to the Co@NC supported ruthenium metal catalyst of 15:1. The conversion rate of benzoic acid was 63.8%, and the selectivity of cyclohexanecarboxylic acid was 75.6%. Figure 1 .

Claims

1. A method for preparing cyclohexanecarboxylic acid by catalyzing the hydrogenation of benzoic acid with a Co@NC-supported ruthenium metal catalyst and its application in the selective hydrogenation reaction of benzoic acid, characterized in that The method steps are as follows: (1) Co@NC structural raw material matrix; (2) reduction with freshly prepared NaBH4 solution and drying; (3) adding benzoic acid and Co@NC loaded ruthenium metal catalyst into a high-pressure reactor, with the mass ratio of benzoic acid to catalyst being 24:1-6; replacing with hydrogen, with the hydrogen pressure being 0.1MPa-2MPa; the reaction temperature being 333K-353K; and the stirring time being 0.5h-1h to obtain the product cyclohexanecarboxylic acid.

2. The Co@NC precursor material prepared in step (1) of claim 1 is selected from cobalt chloride, cobalt bromide, cobalt iodide, cobalt acetate, cobalt carbonate, cobalt sulfate; carboxymethyl cellulose, methyl cellulose, polyvinyl alcohol, sodium alginate, N-methylpyrrolidone; potassium thiocyanide, potassium ferrocyanide, potassium hexacyanocobaltate; four of ethanol, methanol, formamide, and acetone, preferably cobalt acetate, carboxymethyl cellulose, potassium hexacyanocobaltate, and ethanol.

3. According to claim 1, the raw material used in the reduction step (2) is selected from one of potassium borohydride, stannous chloride, oxalic acid and potassium permanganate.

4. The method according to step (3) of claim 1, characterized in that The mass ratio of benzoic acid to the catalyst is 24:(1-6), preferably 24:(2-5).

5. The method according to step (3) of claim 1, characterized in that The reaction temperature is 283K to 433K, preferably 313K to 353K.

6. The method according to step (3) of claim 1, characterized in that The hydrogen pressure of the reaction is 0.1 MPa to 3 MPa, preferably 0.1 MPa to 2 MPa.

7. The method according to step (3) of claim 1, characterized in that The stirring time of the reaction is 0.2 h to 5 h, preferably 0.5 h to 1 h.

Citation Information

Cited By

  • Preparation method of Co-NC nanocube loaded monometal Rh catalyst and application of Co-NC nanocube loaded monometal Rh catalyst in methanol hydrogen evolution

    CN121551048A

  • Preparation method of co-nc nanocube supported monometallic rh catalyst and application thereof in methanol hydrogen evolution

    CN121551048B